2013
DOI: 10.1016/s1734-1140(13)71019-3
|View full text |Cite
|
Sign up to set email alerts
|

Anisomycin suppresses Jurkat T cell growth by the cell cycle-regulating proteins

Abstract: Abstract:Background: Recent studies have shown that anisomycin significantly inhibits mammalian cell proliferation, but its mechanism remains unclear. In this study, Jurkat T cells were used to first explore a relationship between effect of anisomycin on them and alteration of cell cycle-regulating proteins. Methods: Cell colony formation, CCK-8 assay, flow cytometry, RT-PCR and western blot were employed to evaluate correlation of ten cell cycle-regulating proteins with suppression of the cell proliferation a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 28 publications
1
15
0
Order By: Relevance
“…Since cancer stem cells are resistant to most traditional chemotherapeutic drugs, such as cisplatin and paclitaxel, it is necessary to develop more effective drugs for tumour chemotherapy (21,(29)(30)(31). Anisomycin has been confirmed to have significant inhibitory effects on a variety of solid tumours and is a promising chemotherapeutic drug candidate (7)(8)(9)(10)(11). Our previous report has revealed that anisomycin inhibits the proliferation and invasion of ovarian cancer stem cells by enhancing the activity of lncRNA-BACE1-AS and increasing the release of endogenous Aβ42 (7).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Since cancer stem cells are resistant to most traditional chemotherapeutic drugs, such as cisplatin and paclitaxel, it is necessary to develop more effective drugs for tumour chemotherapy (21,(29)(30)(31). Anisomycin has been confirmed to have significant inhibitory effects on a variety of solid tumours and is a promising chemotherapeutic drug candidate (7)(8)(9)(10)(11). Our previous report has revealed that anisomycin inhibits the proliferation and invasion of ovarian cancer stem cells by enhancing the activity of lncRNA-BACE1-AS and increasing the release of endogenous Aβ42 (7).…”
Section: Discussionmentioning
confidence: 99%
“…The present study suggested that anisomycin may have the potential to inhibit cancer stem cells. Based on the existing reports (7)(8)(9)(10)(11), it was speculated that the inhibitory effect of anisomycin on cancer stem cells may depend on multi-target regulation. Therefore, it is meaningful to explore its in-depth mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5), have been also reported to efficiently affect UHRF1 expression [111, 112]. Nevertheless, the mechanism of UHRF1 downregulation induced by natural compounds that target the signaling pathways of UHRF1 expression remains to be deciphered, but might involve the proteasome pathway.…”
Section: Signalling Pathways Involved In Uhrf1 Regulation In Cancer Cmentioning
confidence: 99%
“…A recent study showed that inhibition of microRNA-20a expression increases APP expression and suppresses ovarian cancer cell proliferation and invasion (10). Similarly, other studies indicate that anisomycin, a small molecule antibiotic, can inhibit the proliferative and invasive ability of some tumor cells by increasing the production of the toxic amyloid β (Aβ1-42) peptides from APP (11,(15)(16)(17)(18)(19). In particular, anisomycin [2-(p-methoxybenzyl)-3,4-pyrrolidinediol-3-acetate] increases mRNA expression of APP, β-site APP cleaving enzyme 1 (BACE1 or β-secretase) and presenilin 1 (PS1) in a human SH-SY5Y cell line (10).…”
Section: Introductionmentioning
confidence: 99%